PROLONGED OUTPATIENT MECHANICAL VENTILATION AND INTENSIVE CARE IN PATIENT WITH AMYOTROPHIC LATERAL SCLEROSIS. CASE REPORT - Пугачев, Станислав Валерьевич; Каменева, Евгения Александровна; Шалякина, Надежда Юрьевна; Ануфриева, Наталья Александровна; Григорьев, Евгений Валерьевич; Мозес, Вадим Гельевич (Medicine in Kuzbass, 2020)
Amyotrophic lateral sclerosis (ALS) is rare neurodegenerative disease that needs prolonged respiratory therapy. Ventilator respiratory support is strongly requested for intensive care in different critical illnesses, but it is associated with high risk of specific complications. Latter could rarely be avoided especially in cases of prolong mechanically ventilation that provided in cases of central nervous system injury, major trauma, persisting organ dysfunction etc. Despite the fact of incurable loss of spontaneous breathing in patients with ALS, logistic path of outpatient palliative care provision is absent. Nonetheless outpatient individual intensive care, for respiratory tract particularly, makes possible to avoid serious ventilator-associated adverse events for a long period.